A second‐generation capture panel for cost‐effective sequencing of genome regulatory regions in wheat and relatives. Issue 1 (9th December 2022) - Zhang, Junli; Debernardi, Juan M.; Burguener, Germán F.; Choulet, Frédéric; Paux, Etienne; O'Connor, Lauren; Enk, Jacob; Dubcovsky, Jorge
Abstract: As genome resources for wheat ( Triticum L.) expand at a rapid pace, it is important to update targeted sequencing tools to incorporate improved sequence assemblies and regions of previously unknown significance. Here, we developed an updated regulatory region enrichment capture for wheat and other Triticeae species. The core target space includes sequences from 2‐Kbp upstream of each gene predicted in the Chinese Spring wheat genome (IWGSC RefSeq Annotation v1.0) and regions of open chromatin identified with an assay for transposase‐accessible chromatin using sequencing from wheat leaf and root samples. To improve specificity, we aggressively filtered candidate repetitive sequences using a combination of nucleotide basic local alignment search tool (BLASTN) searches to the Triticeae Repetitive Sequence Database (TREP), identification of regions with read over‐coverage from previous target enrichment experiments, and k‐mer frequency analyses. The final design comprises 216.5 Mbp of predicted hybridization space in hexaploid wheat and showed increased specificity and coverage of targeted sequences relative to previous protocols. Test captures on hexaploid and tetraploid wheat and other diploid cereals show that the assay has broad potential utility for cost‐effective promoter and open chromatin resequencing and general‐purpose genotyping of various Triticeae species. Core Ideas: Regulatory regions contain variation that is valuable for crop improvement. Promoter regions and open chromatin regions are enriched in regulatory elements. A new target enrichment assay facilitates cost‐effective regulatory region sequencing in wheat and relatives. The new assay improves in scope and performance by incorporating new target space and avoiding repetitive elements.